The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0363546514563281
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interobserver Agreement in the Classification and Treatment of Distal Third Clavicle Fractures

Abstract: Fracture stability determination and the decision to operate had the highest interobserver agreement. Fracture stability was the key determinant of treatment, rather than the Neer classification system or the size of the distal fragment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…This may be owed to the preference and the more frequent use of the OTA classification system in the daily business in the group of trauma surgeons. While all investigators in this study were independent and experienced consultants, either in the field of musculoskeletal radiology or in the field of trauma surgery, these results are concordant with the results of other reliability evaluating studies [14], that emphasized the importance of assignment of experts to test the classification system itself [30]. Furthermore, it underscores the need for both a meticulous clinical examination as well as imaging in determining individualized treatment options.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This may be owed to the preference and the more frequent use of the OTA classification system in the daily business in the group of trauma surgeons. While all investigators in this study were independent and experienced consultants, either in the field of musculoskeletal radiology or in the field of trauma surgery, these results are concordant with the results of other reliability evaluating studies [14], that emphasized the importance of assignment of experts to test the classification system itself [30]. Furthermore, it underscores the need for both a meticulous clinical examination as well as imaging in determining individualized treatment options.…”
Section: Discussionsupporting
confidence: 84%
“…Bishop et al [14] demonstrated fair interobserver agreement among 22 shoulder/sports medicine fellowship-trained orthopedic surgeons when using the Neer classification system for lateral clavicle fractures. Cho et al [13] also rated the inter- and intraobserver agreement among nine shoulder specialists and nine orthopedic fellows as fair when using the modified Neer classification system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is difficult to draw firm conclusions on the usefulness of this parameter. Overall interobserver agreement for assessment of morphologic features of a middle phalanx base fracture was much greater than other anatomic areas (humerus, elbow, clavicle, and olecranon) [1,2,5,8,10]. We found only fair agreement, indicating variation, regarding specific proposed treatments, which might be a reflection of the lack of high-level evidence and relatively small case series on which surgeons base their decisions [7].…”
Section: Discussionmentioning
confidence: 69%
“…Putting aside whether the criteria for recommending operative treatment of a proximal interphalangeal joint fracturedislocation are useful and accurate thresholds, if observers cannot agree on the criteria (unreliable) they may not be useful. Studies of fractures at other anatomic sites (such as the humerus, clavicle, and olecranon) showed that some fracture characteristics are assessed more reliably than others [1,2,5,8,10]. In addition to measuring the reliability of radiographic criteria for recommending operative treatment, better understanding of the criteria that have the greatest influence on recommendation for treatment of middle phalanx base fractures would help direct the development of guidelines and measurement techniques for those criteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, fracture type does not always determine individual surgical indications or implant selection. A study by Bishop et al 28 showed that the decision to operate on distal clavicle fractures was largely determined by the surgeon's assessment of fracture stability rather than the Neer classification or the size of the distal clavicle fracture fragment. Another consideration is that the indications for standard clavicle plates vs hook plates are variable, making direct comparison of treatment groups and outcomes difficult.…”
Section: Limitationsmentioning
confidence: 99%